The impact of classified and unclassified techniques on the male medalists' offensive activity at the 2004-2016 Olympic Games - AMAR AIT ALI YAHIA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: Judokas have thrown opponents using various techniques. The researchers' interest in the classified technique remained relevant. No previous study has investigated the contribution of an unclassified technique to high-level judo. Aim: This work assessed the share of classified and unclassified techniques of Nage-waza on the volume of attack activity, technical repertoire, and effectiveness of medalists at Athens 2004, Beijing 2008, London 2012, and Rio de Janeiro 2016. Material and methods: The analysis focused on 3,664 Nage-waza actions, including 2,146 classified actions and 1,518 unclassified actions, performed by 112 male medalists in 575 contests. Anderson-Darling test assessed the normality of the collected data. Multiple comparisons via t Student, one-way analysis of variance, and Tukey post hoc test verified the medalists' offensive activity. Cohen's estimator d and unbiased estimator ω2 tested the size effect of the analysis of variance. Results: To achieve such performances, medalists attempted 19.2±10.0 classified attacks and 13.6±10.5 unclassified attacks. Their effectiveness involved 2.6±1.8 classified actions and 2.0±1.8 unclassified actions, using a repertoire of 7.4±3.0 classified techniques and 4.2±2.6 unclassified techniques. Conclusions: Judicious combination of both techniques contributes to the medalists' performance. Integrating unclassified ones as part of the training and preparedness of judokas was a prior inescapables.